Evaluating the performance of government tourism facilities using ABC and EVA techniques / Case Study - KUHAIT, AMAL ABDULHUSSAIN; HABEEB, FADHEL ALLAH AHMED ABED AL; ANNON, SHEHLAA NEAMAH (The journal of contemporary issues in business and government, 2021)
This study aims to measure cost and performance under the Activity Based Costing (ABC) technique with the economic value-added financial performance measure. The proposed ABC-and-EVA is an administrative support tool for cost and capital management. The integrated ABC-and-EVA input includes resource consumption rate as in traditional ABC technology, but it also includes capital resources. It is done by examining the cost of each activity in the first stage. The company’s capital information is then converted into capital charges to discuss the changes in final product costs and potential changes in performance.